Modified Timed Efficient Stream Loss-tolerant Authentication to Secure Power Line Communication - Boyce Sigweni; Mmoloki Mangwala; Joseph Chuma (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper investigates the feasibility of Timed Efficient Stream Loss-tolerant Authentica- tion to serve security needs of Power Line Communication (PLC) system. PLC network has been identified as the ideal choice to function as the last mile network, deliver load management messages to smart meters. However, there is need to address the security concerns for load management messages delivered over power line communications. The ubiquitous nature of the power line communication infrastructure exposes load management systems (LMS) deployed over it to a security risk. Ordinarily, PLC network does not em- ploy any security measures on which the smart meters and data concentrators can depend on. Therefore, the need to provide a secure mechanism for communication of load man- agement system messages over a PLC network. In LMS, source authentication is of highest priority because we need to respond only to messages from an authenticated source. This is achieved by investigating suitable robust authentication protocols. In this paper we present modifications to Timed Efficient Stream Loss-tolerant Authentication for secure authentica- tion to secure messages for load management over PLC. We demonstrate that PLC can be used to securely and effectively deliver Load Management messages to smart meters, with minimal overhead.